HUBUNGAN PROMOSI DAN PELAYANAN GO-FOOD SERTA PERILAKU KONSUMSI PANGAN OBESOGENIK DENGAN STATUS GIZI LEBIH REMAJA - Amanda Alifa; Dian Luthfiana Sufyan; Ikha Deviyanti Puspita (Poltekkes Kemenkes Semarang, 2020)
Background : Adolescence is a period that is easily influenced by external factors and easy to follow the trends such as online food ordering that is evolve. Adolescent consumption habits are now classified as unhealthy, such as consuming fast food and sweetened beverages that if consumed continuously, excessively, and without physical activity can lead to obesity.Subject : This study aimed to determine the correlation between GoFood promotion, GoFood service, and obesogenic food consumption behavior with adolescent nutritional status (overweight and obesity) at RW 02 Cilandak Barat.Method : The study used a cross sectional design with chi-square test method. Assessment of GoFood promotion and GoFood service using questionnaires, and consumption of obesogenic food using FFQ (Food Frequency Questionnaire), and anthropometric measurements included weight and height for 64 adolescents.Result : The analysis showed that GoFood promotion (p = 0,880), GoFood service (p = 0,149), and consumption of obesogenic food (p = 0,773) have no correlation (p 0,05) with overweight and obesity.Conclusion : There was no correlation between GoFood promotion, GoFood service, and obesogenic food consumption behavior with adolescent nutritional status (overweight and obesity) at RW 02 Cilandak Barat.